If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (84 + -2x)(70 + 5x) = y Multiply (84 + -2x) * (70 + 5x) (84(70 + 5x) + -2x * (70 + 5x)) = y ((70 * 84 + 5x * 84) + -2x * (70 + 5x)) = y ((5880 + 420x) + -2x * (70 + 5x)) = y (5880 + 420x + (70 * -2x + 5x * -2x)) = y (5880 + 420x + (-140x + -10x2)) = y Combine like terms: 420x + -140x = 280x (5880 + 280x + -10x2) = y Solving 5880 + 280x + -10x2 = y Solving for variable 'x'. Combine like terms: y + -1y = 0 5880 + 280x + -10x2 + -1y = 0 The solution to this equation could not be determined.
| 3t=7y | | 2lx-3l+3=11 | | 84=28y+12x | | 3x^2+24=12 | | -x=0.69 | | W+13=11w-7 | | -13-2x=5(1+4x) | | 19.36+2.6d=d | | 7(x+1)-6(x+3)=0 | | 4(q-1)=6q-12 | | -14-15+g=-2g+16 | | m-38=-34 | | 3X-2+0.5X+X=21-2+X | | -4(3S)=-36 | | z+27=27 | | 3X-2+0.5+X=21-2+X | | (-4)(-2)-6(2-5)=x | | 1.5x=3.5 | | 10p-2=10(p+1)-7 | | 5n+82=47 | | 10p-2=10(p+1)-17 | | 6j-20=8j | | 8(-3-9x)=7(5x+2-x) | | 5x=5y-9 | | 0.5X+2-2.5X=1.5X-6 | | -20+7b=9b | | 9-a=3 | | 4a+2ai+4bi-2bi^2=40 | | 39-3(x+5)=3x+6 | | F(x)=5x^4-13x^2+36 | | -12.3+13.07+11.5y=10.03+0.8y | | x+3x+6x=65 |